Development of new perennial oil crops for marginal environments : productivity of Lesquerella mendocina under different nitrogen availability - Ploschuk, Edmundo Leonardo (2010)
Fil: Ploschuk, Edmundo Leonardo. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Producción Vegetal. Cátedra de Cultivos Industriales. Buenos Aires, Argentina.